(untitled) (Journal of Naval Architecture and Marine Engineering, 2014)
Water impact phenomenon of general bow section is a critical event for planning hulls. In this paper, the water entry of several arbitrary bow sections is investigated. For this purpose, arbitrary bow shapes which are introduced by Lewis form approximation are considered. In order to obtain pressure distribution and free surface profile, volume of fluid (VOF) method coupled with finite volume method (FVM) are utilized in Ansys-CFX solver. The main feature of present study is consideration of some new arbitrary bow sections which have not been previously studied. Another motivation of the current work is investigation of water entry of arbitrary bow sections using a coupled numerical solution of FVM/VOF. Pressure distribution, free surface, and evolution of intersection point on bow sections are presented, while secondary water impact is demonstrated. Comparison of selected current findings against the results of previous studies indicates favorable agreement. DOI: http://dx.doi.org/10.3329/jname.v11i2.18724